Assessing the importance of kelp forests for small-scale fisheries under a global change scenario - Piñeiro-Corbeira, Cristina; Barrientos, Sara; Barreiro, Rodolfo; de la Cruz-Modino, Raquel (Frontiers in Marine Science, 2022)
Kelp forests are critical habitats for temperate coasts that are experiencing dramatic declines worldwide in recent decades. Yet, even though they often support wildlife populations of high socioeconomic value, the consequences of kelp forest decline for Small-Scale Fisheries (SSF) have received surprisingly little attention. Here, we take the first step to fill this gap through the local ecological knowledge (LEK) of SSF fishers whose fisheries are associated with this habitat in NW Spain. LEK was used to (i) estimate kelp forests loss, (ii) identify the main fisheries associated with kelp forests, (iii) gain insight into the changes these fisheries may have undergone in recent times iv) evaluate the economic importance of kelp in the study area, v) describe the commercial chain of exploited kelps and relevant fisheries related to them. Fisher’s knowledge of kelp forests was documented through interviews with the help of a semi-structured questionnaire with open-closed questions about the small-scale fishery and its target species. Additionally, participants were asked to map the current and former (20 years ago) distribution of kelp forests in their fishing area. Results show that a range of fish, crustaceans, mollusks, echinoderms, and even the kelp itself are fished/harvested in the study area, suggesting the socioeconomic value of those species. The most intensively targeted species usually belong to fisheries with high commercial value and first-sale data indicate that they are worth some ten million euros to the local economy. On the other hand, compared to two decades ago, fishers reported a substantial contraction in the area occupied by kelp forests and decreases in the fisheries typically associated with this habitat. Landing data partly support this perception of a decline in catches. Altogether, this information will be useful to foster kelp forest conservation and to evaluate their socio-ecological and economic implications for SSF.